Philodendron josephii (Araceae), a new species from central Amazonia, Brazil - Batista, Caio Augusto Dos Santos; Soares, Maria De Lourdes Da Costa (Phytotaxa, 2023)
Philodendron josephii sp. nov. is described from terra firme tropical humid forest in Amazonas state, Brazil. This new species is similar in its leaf morphology to two other Amazonian species, P. maximum and P. megalophyllum, but differs by characters of the prophyll, petiole, flagelliform branches and ovary. The description is accompanied by illustrations, notes on the habitat, geographic distribution and conservation status.